Quantifying uncertainties in the high-energy neutrino cross-section - Cooper-Sarkar, A; Mertsch, P; Sarkar, S (Springer, 2012)
The predictions for high-energy neutrino and antineutrino deep inelastic scattering cross-sections are compared within the conventional DGLAP formalism of next-to-leading order QCD, using the latest parton distribution functions (PDF) such as CT10, HERAPDF1.5 and MSTW08 and taking account of PDF uncertainties. From this, a benchmark cross-section and uncertainty are derived which is consistent with the results obtained earlier using the ZEUS-S PDFs. The use of this is advocated for analysing data from neutrino telescopes, in order to facilitate comparison between their results.